1997
DOI: 10.1080/08897079709511365
|View full text |Cite
|
Sign up to set email alerts
|

The Substance‐Abusing Patient and Primary Care: Linkage via the Addiction Treatment System?

Abstract: Our objective was to describe and assess the prevalence and characteristics of substance-abusing persons without primary care physicians. We interviewed a convenience sample at one point in time. Patients/participants were persons presenting for addictions treatment in a public substance abuse treatment system. Of 5824 respondents, 41% did not have a physician. In a multivariable analysis, the following were associated with not having a physician: no health insurance [adjusted odds ratio (OR), 2.05; 95% confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 26 publications
(21 reference statements)
1
23
0
Order By: Relevance
“…24,90 Conversely, patients in medical settings are often not identified or referred to addiction treatment. [91][92][93] In 1991, a Federal conference concluded that better linkage should be pursued by colocating services and improving the effectiveness of referrals. 94 This conclusion remains relevant today.…”
Section: Insufficient Linkage Of Addiction Treatment and Primary Medimentioning
confidence: 99%
“…24,90 Conversely, patients in medical settings are often not identified or referred to addiction treatment. [91][92][93] In 1991, a Federal conference concluded that better linkage should be pursued by colocating services and improving the effectiveness of referrals. 94 This conclusion remains relevant today.…”
Section: Insufficient Linkage Of Addiction Treatment and Primary Medimentioning
confidence: 99%
“…Assessments included demographics, health care utilization, social support, barriers to primary care linkage, beliefs about primary care, substances used, addiction severity (Addiction Severity Index [ASI] alcohol, drug, and psychological sub-scales) (McLellan et al 1992), consequences of drug use (Inventory of Drug Use Consequences ) (Miller and Tonigan 1995), readiness to change substance use (using the Stages of Change Readiness and Treatment Eagerness Scale, [SOCRATES 8AOD]) (Miller and Tonigan 1996), depressive symptoms (Center for Epidemiologic Studies Depression [CES-D] scale) (Radloff 1977), health-related quality of life ) (Ware 1993), and questions regarding comorbid medical diagnoses (Stein et al 1998;Saitz, Mulvey, and Samet 1997).…”
Section: Assessmentsmentioning
confidence: 99%
“…In the distributive pattern, medical and addictions care are delivered in separate locations, and patients and information are transferred from one location to another (Samet, Saitz, and Larson 1996). Yet this flow is anything but seamless (Samet, Friedmann, and Saitz 2001), since receipt of addictions care is not always associated with linkage to primary medical care (Saitz, Mulvey, and Samet 1997). In substance abuse programs opportunities to link patients with primary care are being missed.…”
mentioning
confidence: 99%
See 2 more Smart Citations